Efektivitas Dinas Perpustakaan dan Kearsipan Provinsi Jawa Timur Dalam Meningkatkan Gemar Baca Masyarkat - Vina Qurroti Ainun; Endang Indartuti; Yusuf Hariyoko (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2022)
This study aims to determine the effectiveness of the library and archives service in increasing people's love of reading, based on Law Number 43 of 2007 concerning Libraries, libraries are facilities or places to provide reading materials. The research was made using qualitative method, with an on-site observation process, structured and academically, the data obtained from interviews with related parties, documentation and descriptions. The result showed that, the East Java Provincial Library and Archives Service succeeded in increasing the love of reading for the people of East Java beyond what was targeted in the Strategic Plan. This was due to the active efforts of librarians to continue to invite people to read online and offline and to invite children to make reading a habit. Even so, according to SAKIP, the performance of librarians tends to decline due to the pandemic that hit and remains categorized as good. There are several factors that influence the people's love to read, such as the lack of human resources, the lack of awareness of the people of East Java towards reading and making reading a culture, and the lack of development and development of types of libraries. With the factors that affect reading habits, there are efforts that can be made by the East Java Provincial Library and Archives Service to increase people's reading habits such as socialization and promotion to the public about the importance of reading, increasing the number of human resources, and leveling the development and development of libraries. libraries throughout East Java.